2021
DOI: 10.1111/jop.13124
|View full text |Cite
|
Sign up to set email alerts
|

Sialolipomas of minor salivary glands: A multi‐institutional study and literature review

Abstract: Background Sialolipoma is a rare histological variant of lipoma commonly misdiagnosed and composed of a proliferation of mature adipocytes with secondary entrapment of normal salivary gland tissue. The purpose of the present study is to report the clinicopathologic and immunohistochemical features of 10 new cases of sialolipomas in conjunction with a review of the literature. Methods A retrospective descriptive cross‐sectional study was performed. A total of 54,190 biopsy records of oral and maxillofacial lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In addition, sialolipomas tend to exhibit multiple lobes of fat tissue, with the salivary gland elements uniformly distributed within the fatty component. 2,4 Interestingly, tumors exhibiting both characteristics of OL and sialolipoma have been illustrated by other investigators and described as "oncocytic sialolipomas." 21,34 Pusiol et al 34 reported an interesting case of a probable sialolipoma affecting the submandibular gland with a prominent oncocytic component.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, sialolipomas tend to exhibit multiple lobes of fat tissue, with the salivary gland elements uniformly distributed within the fatty component. 2,4 Interestingly, tumors exhibiting both characteristics of OL and sialolipoma have been illustrated by other investigators and described as "oncocytic sialolipomas." 21,34 Pusiol et al 34 reported an interesting case of a probable sialolipoma affecting the submandibular gland with a prominent oncocytic component.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, sialolipomas tend to exhibit multiple lobes of fat tissue, with the salivary gland elements uniformly distributed within the fatty component. 2,4…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations